A diaphragmatic electrical activity-based optimization strategy during pressure support ventilation improves synchronization but does not impact work of breathing. Issue 1 (December 2017) - Beloncle, Francois; Piquilloud, Lise; Rittayamai, Nuttapol; Sinderby, Christer; Rozé, Hadrien; Brochard, Laurent
Abstract Background Poor patient-ventilator synchronization is often observed during pressure support ventilation (PSV) and has been associated with prolonged duration of mechanical ventilation and poor outcome. Diaphragmatic electrical activity (Eadi) recorded using specialized nasogastric tubes is a surrogate of respiratory brain stem output. This study aimed at testing whether adapting ventilator settings during PSV using a protocolized Eadi-based optimization strategy, or Eadi-triggered and -cycled assisted pressure ventilation (or PSVN ) could (1) improve patient-ventilator interaction and (2) reduce or normalize patient respiratory effort as estimated by the work of breathing (WOB) and the pressure time product (PTP). Methods This was a prospective cross-over study. Patients with a known chronic pulmonary obstructive or restrictive disease, asynchronies or suspected intrinsic positive end-expiratory pressure (PEEP) who were ventilated using PSV were enrolled in the study. Four different ventilator settings were sequentially applied for 15 minutes (step 1: baseline PSV as set by the clinician, step 2: Eadi-optimized PSV to adjust PS level, inspiratory trigger, and cycling settings, step 3: step 2 + PEEP adjustment, step 4: PSVN ). The same settings as step 3 were applied again after step 4 to rule out a potential effect of time. Breathing pattern, trigger delay (Td ), inspiratory time in excess (Tiex ), pressure-time product (PTP), and work of breathing (WOB) were measured at the end of each step. Results Eleven patients were enrolled in the study. Eadi-optimized PSV reduced Td without altering Tiex in comparison with baseline PSV. PSVN reduced Td and Tiex in comparison with baseline and Eadi-optimized PSV. Respiratory pattern did not change during the four steps. The improvement in patient-ventilator interaction did not lead to changes in WOB or PTP. Conclusions Eadi-optimized PSV allows improving patient ventilator interaction but does not alter patient effort in patients with mild asynchrony. Trial registration Clinicaltrials.gov identifier:NCT 02067403 . Registered 7 February 2014.